O01 Recent trends in HIV diagnoses and tests among men who have sex with men attending sexual health clinics in england. (8th June 2017) - Ogaz, Dana; Furegato, Martina; Brown, Alison E; Mohammed, Hamish; Kirwan, Peter; Yung, Mandy; Nash, Sophie; Connor, Nicky; Gill, Noel; Delpech, Valerie; Hughes, Gwenda
Abstract : Introduction: Men who have sex with men (MSM) remain at highest risk of HIV acquisition in England. We assessed recent national trends in HIV diagnoses and tests among MSM attending specialist sexual health clinics (SHCs) in England. Methods: Numbers of HIV diagnoses and tests in MSM were obtained from GUMCADv2, the national surveillance system for sexually transmitted infections. Trends were stratified by HIV testing history (new/repeat-testers in last 2 years) and service location (London/Outside-London). Student's t-tests were used to assess the differences in mean numbers of HIV diagnoses and tests between Q4/2014–Q3/2015 and Q4/2015–Q3/2016. Results: A decline in HIV diagnoses from 515 to 427 (17%) was observed between Q4/2014–Q3/2015 and Q4/2015–Q3/2016 (p=0.05). Greatest declines were in London SHCs (276–209; 24%; p=0.04) and among new-testers (390–308; 21%; p=0.03). In London SHCs, there was a 29% diagnosis decline among new-testers (195–138; p=0.03) with no evidence of a difference in repeat-testers (81–71; p=0.33); HIV tests in repeat-testers increased 15% (9, 768–11, 270; p=0.02) but remained stable among new-testers (7, 166–6, 638; p=0.28). In Outside-London SHCs, HIV diagnoses remained stable in new- (194–170; p=0.06) and repeat-testers (44–48; p=0.52) while HIV testing increased 14% in new- (7, 679–8, 734; p=0.05) and 16% in repeat-testers (7, 423–8, 602; p=0.02). Discussion: HIV diagnoses among MSM have decreased despite overall increased testing at SHCs. Stable levels of testing in new-testers as well as scale-up of repeat-testing may be contributing to diagnosis declines by earlier identification of undiagnosed infections. Further investigation of treatment and prevention initiatives among new- and repeat-testers in London SHCs is necessary.